The Concept of Dependency Game Tree Graphs as a Black Box in the Analysis of Automatic Transmissions - Deptuła Adam; Stosiak Michał; Karpenko Mykola; Łapka Mariusz (Transport and Telecommunication, 2022)
The methodology of graph theory has long had applications in mechanics. Graphs allow the simultaneous consideration and synthesis of the structure of a real system and the idealized structure of an equivalent model of a mechanical system. In particular, there are many applications of graph theory in the analysis of automatic transmissions. This paper presents continuing research on applications of game tree graphs in the analysis of automatic transmissions. Black box ideas for dependency graphs are presented. This makes it possible to automatically generate simplified models from given physical models of an automatic transmission and to determine the optimal number of teeth. The developed methodology allows also to perform real-time simulations. In a further stage, the methods of decision logic trees can be applied to analyze the functional diagrams of selected gears.